2012
DOI: 10.1007/s11136-012-0175-x
|View full text |Cite
|
Sign up to set email alerts
|

Methods for interpreting change over time in patient-reported outcome measures

Abstract: While CDFs serve an important role, they should not be a replacement for the careful investigation of a PRO's relevant responder definition using anchor-based methods and providing stakeholders with a relevant threshold for the interpretation of change over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
157
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(162 citation statements)
references
References 43 publications
4
157
0
1
Order By: Relevance
“…MCIDs were calculated separately for KOOS and SF12v2 PCS as half the SD of all change scores for that specific PROM [30]. Anchor-based methods require a separate subjective assessment measure of a patient's perceived benefit from an intervention, data not collected by our institution's joint replacement registry [47]. The calculated MCID value was 10 for the KOOS and 5 for the SF12v2 PCS (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…MCIDs were calculated separately for KOOS and SF12v2 PCS as half the SD of all change scores for that specific PROM [30]. Anchor-based methods require a separate subjective assessment measure of a patient's perceived benefit from an intervention, data not collected by our institution's joint replacement registry [47]. The calculated MCID value was 10 for the KOOS and 5 for the SF12v2 PCS (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…When investigating the effect of low and high baseline disability (based on the 25th and 75th percentile of the baseline score for ODI), the cutoffs for Table 3 Baseline adjusted mean of the change score, % change score, and final raw score for all PROMS (95% of CI) according to the global perceived effect scale at 1-year follow-up GPE Completely recovered (1) Much better (2) Somewhat better (3) No change (4) Somewhat worse (5) Much worse (6) Worse than ever (7) N (%) 1659 (24) 3265 (48) 1093 (16) 358 (5) 216 (3) 153 (2) 66 (1 ''failure'' and ''worsening'' in the PROMs varied considerably, both for change scores, % change scores, and the final raw score (Table 1x, appendix). For example, in the group with high disability at baseline, the failure cutoff for the mean % change in ODI was 30% higher than in the low disability group.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Still, clinicians are often unfamiliar with their interpretation. In large cohorts, even small and clinically irrelevant PROM changes tend to reach statistical significance [4]. To provide cutoffs on PROM changes that are perceived as meaningful and important by the patients, the ''minimal important change'' (MIC) has been defined by various methods [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…7 However, despite the draft PRO Guidance clearly distinguishing between the importance of change within-patient and between-group, the term ''MID'' is sometimes erroneously used for these 2 concepts interchangeably. Given the long history, inconsistent use, and vagueness of ''minimal,'' some PRO experts have suggested that we eliminate the terms ''MID'' and ''MCID'' from our vocabulary (Figure 1).…”
Section: A Select History Level Of Measurementmentioning
confidence: 99%